Vulnerability and retrofitting of torsionally deformable RC buildings: A case study. (August 2021) - Mulas, Maria Gabriella; Stroffolini, Lorenzo; Martinelli, Paolo
Abstract: The paper presents the seismic vulnerability assessment and the subsequent retrofitting strategies of a reinforced concrete (RC) strategic building in Italy. At time of design, the erection site was not classified as a seismic area. With a structural layout widely spread in non-seismic zones and for buildings designed with obsolete seismic codes, the framed system was designed for gravity loads only, with an eccentric lift core and moment-resisting frames aligned in one direction. The structural seismic capacity is impaired by torsional deformability and the possible appearance of both brittle collapse mechanisms and pounding phenomena with an adjacent building, while the seismic demand is governed by the classification of "strategic building". Two retrofitting strategies are here analysed, under the constraints of eliminating the torsional deformability and minimizing the interruption of normal activities in the building. The results highlight the advantages and disadvantages of the two strategies and the most important features of the structural response, providing indications for further actions. The adoption of a design spectrum reduced by a 0.6 factor, roughly equivalent to that for an ordinary building, extends the relevance of the work well beyond the case study.